ANALISIS EFEKTIVITAS DAN KONTRIBUSI PAJAK REKLAME TERHADAP PENDAPATAN ASLI DAERAH DI KOTA PONTIANK - Diki, Ignasius; Jaurino; Sari, Wilda (Program Studi Akuntansi Universitas Panca Bhakti, 2022)
This study focuses on the analysis of the effectiveness and contribution of advertising tax to localrevenue in Pontianak City, which aims to determine the effectiveness of the realization ofadvertisement tax revenue and how much advertising tax contributes to local revenue in PontianakCity. This study uses the method of observation, interviews and documentation directly to thePontianak City Regional Finance Office.Data collection using observation, interviews anddocumentation methods aims to determine the level of effectiveness and contribution of advertisingtax to local revenue in Pontianak City. The data analysis technique used is effectiveness ratioanalysis technique, contribution ratio analysis technique and trend analysis. Based on the resultsof the analysis of the effectiveness and contribution of advertising tax to local revenue in PontianakCity, it has been very effective with the contribution of advertising tax to local revenue is still veryless. The identified factors that affect effectiveness and contributions are willingness to pay taxesand the existence of advertisements that have expired.